(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2016)
Education process needs costs. Problems of education financing are still struggling on the sources of the cost of education, management education costs, and the allocation of the cost of education, as well as the cost-efficiency of education. The policy of Permendiknas 69 / 2009 is a policy that answer education financing. The policy was studied through formul ati on anal ysi s, Material /Content, Implementation and Evaluation. The fact suggests that Permendiknas 69 / 2009, regulates the costs operating that only lasted for one year, for year 2009 Using the DKI Jakarta bases. It does not regulate i nvestment costs, and personnel costs yet. Therefore, the determination of costs every year is needed, and preferably before the new school year.